Covid-19 and Neurology - Şerefnur Öztürk (Türk Nöroloji Dergisi, 2020)
Neurological diseases are the most common and important health burden over the world. Coronavirus disease-19 (COVID-19) pandemic is a new and important burden for the neurological area. Information related to the neurological involvement of Severe Acute Respiratory syndrome-Coronavirus-2 infection has been increased during the last several months. Frequency and mechanisms of neurological involvement of the disease may be explained more efficiently by neurologists who are included within the multidisciplinary COVID-19 teams. Other very important point is possibility of failure of follow up and treatment of chronic neurological disorders which needed frequent and regular control and also quick action for the acute treatment. The regulations are extremely important for the neurologists to perform their responsibilities with considering all these requirements.